Deletion of Galectin‐3 attenuates acute pancreatitis in mice by affecting activation of innate inflammatory cells. Issue 6 (2nd April 2019) - Stojanovic, Bojan; Jovanovic, Ivan; Stojanovic, Bojana S.; Stojanovic, Milica Dimitrijevic; Gajovic, Nevena; Radosavljevic, Gordana; Pantic, Jelena; Arsenijevic, Nebojsa; Lukic, Miodrag L.
ABSTRACT: Acute pancreatitis is characterized by autodigestion of pancreatic cells followed by acute inflammation leading to pathology and death. In experimental acute pancreatitis, pancreatic acinar cells and infiltrating macrophages express Galectin‐3 but its role in pathology of this disease is unknown. Therefore, we studied its role using Galectin‐3 deficient mice. Deletion of Galectin‐3 prolonged the survival of mice, led to attenuation of histopathology, and decreased infiltration of mononuclear cells and neutrophils that express TLR‐4, in particular, pro‐inflammatory N1 neutrophils. Galectin‐3 and TLR‐4 are also colocalized on infiltrating cells. Lack of Galectin‐3 reduced expression of pro‐inflammatory TNF‐α and IL‐1β in F4/80 + CD11c‐ and CD11c + F4/80 − cells. Thus, deletion of Galectin‐3 ameliorates acute pancreatitis by attenuating early influx of neutrophils and inflammatory mononuclear cells of innate immunity. These findings provide the basis to consider Galectin‐3 as a therapeutic target in acute pancreatitis. Abstract : Galectin‐3 deletion attenuates acute pancreatitis due to lack of galectin‐3 interaction with TLR‐4 after initial BPD‐induced destruction of acinar cells and a decrease in production of pro‐inflammatory cytokines by N1 neutrophils, macrophages, and dendritic cells.